'Nature in League with Man': Conceptualising and Transforming the Natural World in Eighteenth-Century Scandinavia. (1st August 2004) - Oslund, Karen
This article examines a series of projects and discussions, among the Enlightenment elite in the Danish kingdom, about the need for technological improvement and agricultural reform in Iceland, a distant province of the Danish state in the eighteenth century. One of the most important of these projects was the importation of reindeer from northern Norway to Iceland in the latter half of the eighteenth century, in response to famine conditions and plagues that had decimated the sheep population on the island. These projects and the language that their instigators and supporters used show that the Enlightenment elite sought to re-define Icelandic and Northern nature, reclaim a territory that had been historically viewed as a wilderness, and remodel it into a well-regulated and homogeneous part of the state. Their vision of nature in the North Atlantic was a radical break with previous traditions of describing nature in Iceland and one of the first times that Icelanders sought to establish themselves as authorities about conditions in their country.